A Solution to the Next Release Problem by Swarm Intelligence - Qassem , Deema Yahya; Al_saati, Najla Akram (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
First of all, in this research, we solve the problem of the next release ((NRP) (Next Release Problem)), which is classified as a multi-objective difficult problem (NP_ hard problem) using swarm intelligence, since the programs are spread in all areas of our life and process The development on it is constantly ongoing and the selection of the optimal requirements to satisfy customers for the following versions is a very important process, as the requirements that have been dealt with are complicated due to interdependence and other limitations. Therefore, we will highlight it in our research to solve it, as the problem of the next release (NRP) is defined as a multi-objective improvement problem with two conflicting goals, which are customer satisfaction and development cost, and since it is a multi-objective problem, we chose swarm intelligence to solve it, where we solved This problem using the Multi_objective Mayfly Algorithm is derived from the behavior of the swarms of the Mayfly in nature.